Integrating Signal Transduction Mechanisms and Therapeutic Strategies in Cancer - Aqeel Ahmad; Amer Ali Khan; Faiyaz Ahmad; Nemer Alotaibi; Noureldaim Elnoman Elbadawi (Achievements and Challenges of Medicine and Medical Science Vol. 11, 2025)
This book chapter discusses a wide range of the various signaling pathways involved in cancer biology. Much importance has been given to cellular signaling in controlling basic processes like cell proliferation, differentiation, and apoptosis and how its deregulation leads to tumor development. This study puts great stress on major pathways implicated in cancer, including the MAPK/ERK, PI3K/AKT, JAK/STAT, and Wnt/\(β\)-catenin pathways, and presents how aberrant activation of these pathways leads to uncontrolled proliferation, survival, and metastasis. Among these, epigenetic mechanisms involve DNA methylation and histone abnormalities, which have become important in the process of carcinogenesis through mechanisms including, but not limited to, the aspects of gene expression and/or signaling pathways. Aberrant methylation contributes to tumor suppressor gene silencing, while histone modifications might include the activation of oncogenes or active repression of critical pathways. These could contribute to carcinogenesis by promotion, escaping apoptosis, and metastasis. Targeting these epigenetic processes is an interesting therapeutic perspective in cancer therapy. The chapter reviews some of the history of the research in signal transduction and discusses recent findings that have reshaped the face of cancer treatment, including so-called targeted medicines such as kinase inhibitors and monoclonal antibodies. This review discusses the impact of the tumor microenvironment on signal transduction, with a primary focus on how this impacts cancer cell behavior and resistance to therapies. It further discusses the role of post-translational modifications in controlling signaling networks. Other future strategies involve the integration of systems biology and network pharmacology for the improvement of multi-target medicines, while the use of techniques from personalized medicine is based on special signaling patterns. The authors conclude that further technological development of single-cell sequencing and artificial intelligence could fine-tune cancer therapeutic strategies and give an edge over drug resistance. This comprehensive evaluation identified the importance of a multifaceted approach in cancer for improved treatment outcomes and precision oncology.